1997
DOI: 10.1002/(sici)1096-9861(19970526)382:1<104::aid-cne7>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of GAP-43 immunoreactivity in the auditory brainstem of the rat

Abstract: Extensive data link the growth associated protein GAP-43 to axonal elongation and synapse formation during development and in plastic responses of nervous tissue. We have studied the changing levels of GAP-43 expression in the auditory brainstem nuclei of the developing rat by applying immunocytochemical techniques. By the first postnatal day (P1), GAP-43 was expressed at high concentrations in all subdivisions of the cochlear nuclear complex and the superior olivary complex. At this stage, neuropil structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…On the basis of GAP-43 labeling, Horvath et al (1997) concluded that synapses in the cochlear nucleus are formed by about P8. The electron microscopic data in the present study support the conclusion that synapses are morphologically mature by P8.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of GAP-43 labeling, Horvath et al (1997) concluded that synapses in the cochlear nucleus are formed by about P8. The electron microscopic data in the present study support the conclusion that synapses are morphologically mature by P8.…”
Section: Discussionmentioning
confidence: 99%
“…59 In the auditory brainstem, high levels of GAP-43 protein are evident in all subdivisions of the cochlear nuclear complex and the superior olivary complex at PND0. 60 Between PND8 and PND12, the GAP-43 staining pattern in these regions became punctate, indicating the formation of presynaptic endings. By PND16, the auditory brainstem nuclei appear mostly devoid of GAP-43 immunoreactivity, with the exception of staining localized to presynaptic terminals.…”
Section: Relationship To Developmentmentioning
confidence: 99%
“…By PND16, the auditory brainstem nuclei appear mostly devoid of GAP-43 immunoreactivity, with the exception of staining localized to presynaptic terminals. 60 In the cat visual cortex, phosphorylation of GAP-43 increased approximately 10-fold from PND1 to weeks 3-13 (the critical period of synaptic plasticity) then decreased to 2.5-fold of PND1 by week 51. 61 Protein quantification of GAP-43 in the cortex and hippocampus was elevated at PND14 and PND21 during an active period of synaptogenesis.…”
Section: Relationship To Developmentmentioning
confidence: 99%
“…Peak expression before mature synapse formation (P0-P5) suggests either a non-synaptic role for 7 nAChRs or the early presence of synapses. Synapses at these early ages are not expected, because GAP-43, a marker of growth cones, is still heavily expressed (Horvath et al, 1997). In the nuclei of the lateral lemniscus and the lateral periolivary nucleus, peak expression (P15-20) coincides with a transitional maturation period after the onset of hearing.…”
Section: Developmental Prowles For 7 In Soc Ic and Llmentioning
confidence: 99%
“…There are no available data indicating when synapses are Wrst formed in the VCN, but it is probable that synapses are not present in the VCN at birth. DiVuse GAP-43 labeling before P8 in the rat suggests that growth cones are still predominant (Horvath et al, 1997).…”
Section: Developing Vcn: 3 4 Nachrsmentioning
confidence: 99%